Insight into SMEs growth in Singapore - Ang, Li Chin (2008)
This paper examines three major functions namely, entrepreneur’s attributes, firm’s characteristics and strategic orientation of the firm that contributes to SME growth. Interpretations of these functions are discussed and recommendations for future research directions are proposed.